2013
DOI: 10.1007/s11262-013-1010-3
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping genotype 2 hepatitis C viruses from Tunisia: identification of two putative new subtypes

Abstract: HCV variants were classified into six genotypes (1-6) subdivided into several subtypes with different geographic distribution worldwide. Previous studies conducted in Tunisia showed that genotype 1 counts for more than 80 % of circulating HCV genotypes and most of the isolates belong to subtype 1b. Genotype 2 comes in the second position, however, few sequences have been analyzed and published. In the present study, 89 isolates from Tunisian patients, typed as genotype 2 by the InnoLIPA commercial probe hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The frequency of HCV-2c varies from one country to another. Although not very common in Brazil, Canada, Chile, Mexico, or the USA [ 37 , 38 ], HCV-2c is the second most frequently isolated after genotype 1 in Argentina [ 39 ], Italy [ 40 ] and in Tunisia [ 19 ]. In the present work, we analyzed the genetic diversity and the phylogenetic relatedness between the NS5B sequences within HCV-2c subtype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of HCV-2c varies from one country to another. Although not very common in Brazil, Canada, Chile, Mexico, or the USA [ 37 , 38 ], HCV-2c is the second most frequently isolated after genotype 1 in Argentina [ 39 ], Italy [ 40 ] and in Tunisia [ 19 ]. In the present work, we analyzed the genetic diversity and the phylogenetic relatedness between the NS5B sequences within HCV-2c subtype.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of the phylogenetic constructions was estimated by bootstrap analysis with 1000 pseudo replicate data sets. Sixty-eight out of the 113 Tunisian sequences included in the present study were previously published in GenBank [ 19 ] whereas 45 sequences are new and reported for the first time in this study; they were submitted to GenBank under the accession numbers KJ206290 to KJ206333 and KJ206335. In addition, ninety-two HCV field sequences, published in GenBank and isolated from different countries in the world were included in these phylogenetic analyses: 53 isolates from Subtype 2c and 39 isolates from subtype 2k.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation